2016
DOI: 10.1016/j.cell.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Hybridization of Glucagon and Thyroid Hormone Optimizes Therapeutic Impact for Metabolic Disease

Abstract: Glucagon and thyroid hormone (T) exhibit therapeutic potential for metabolic disease but also exhibit undesired effects. We achieved synergistic effects of these two hormones and mitigation of their adverse effects by engineering chemical conjugates enabling delivery of both activities within one precisely targeted molecule. Coordinated glucagon and T actions synergize to correct hyperlipidemia, steatohepatitis, atherosclerosis, glucose intolerance, and obesity in metabolically compromised mice. We demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
133
0
10

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(149 citation statements)
references
References 56 publications
3
133
0
10
Order By: Relevance
“…Nevertheless, the hepatic action of T3 to improve lipid metabolism renders T3 a validated candidate for more advanced pharmacological approaches. Consistent with this perspective, and as discussed later in this review, a novel strategy entails the recruitment of a peptide hormone to preferentially deliver T3 to the liver (Finan et al, 2016a).…”
Section: A Thyroid Hormonesmentioning
confidence: 80%
See 2 more Smart Citations
“…Nevertheless, the hepatic action of T3 to improve lipid metabolism renders T3 a validated candidate for more advanced pharmacological approaches. Consistent with this perspective, and as discussed later in this review, a novel strategy entails the recruitment of a peptide hormone to preferentially deliver T3 to the liver (Finan et al, 2016a).…”
Section: A Thyroid Hormonesmentioning
confidence: 80%
“…Studies using glucagon receptor knockout mice confirmed the receptor selectivity in the conjugate and provides indirect evidence that the glucagon receptor is a necessary ingredient to T3 transport and biologic action. As a result of this hepatictargeted biodistribution profile, the glucagon-T3 conjugate dose-dependently corrected dyslipidemia in various rodent models of dietary-induced metabolic syndrome, most notably mice fed HFD and Western-style diets (Finan et al, 2016a). Importantly, the benefits on lipid metabolism were muted when studied in mice with selective hepatic knockout of TRb, demonstrating the tissue and target selectivity of the conjugate.…”
Section: B Glucagon-mediated Delivery Of Thyroid Hormone Tri-iodothymentioning
confidence: 85%
See 1 more Smart Citation
“…Our results indicate that interventions based on the use of THs or thyromimetics could open novel venues for the treatment of T1DM. Whereas novel treatments including the use of T4 supplementation might not be optimal for the treatment of metabolic diseases due to side effects, certain newly developed thyromimetics could affect specific cell types or organs that could benefit from these actions of THs, resulting in the improvement of metabolic homeostasis, while avoiding side effects (Shoemaker et al, 2012;Coppola et al, 2014;Finan et al, 2016). Although the profound systemic effects of the T4-administration in mice suggest that THs and thyromimetics might be useful in ameliorating the abnormal metabolism in diabetic patients, the identification of the underlying mechanisms that are critical for the observed improvements on glucose control and potential long-term toxic effects must be addressed before results in mice could be extrapolated to humans.…”
Section: Discussionmentioning
confidence: 99%
“…The average activity of T3 is about three to five times higher than T4, but the stability is 19 h in euthyroid patients. Other THs or thyromimetics, such as triac, tetrac, thyrinnamines, reverse T3, 3,5-diiodo-l-thyronin and conjugated glucagon/T 3 , also exist and are recently attracting attention in the scientific community as promising drugs for the treatment of several pathologies (Ball et al, 1997;Shang et al, 2013;Goglia, 2014;Senese et al, 2014;Finan et al, 2016). One of the main physiological roles of THs is the regulation of basal metabolic rate, defined here as the rate of energy expenditure per time at rest, which accounts for about 60-75% of the calories burned in a healthy subject.…”
Section: Introductionmentioning
confidence: 99%